2008
DOI: 10.1209/0295-5075/81/56003
|View full text |Cite
|
Sign up to set email alerts
|

Protein adsorption kinetics in different surface potentials

Abstract: We have studied the adsorption kinetics of the protein amylase at solid/liquid interfaces. Offering substrates with tailored properties, we are able to separate the impact of short- and long-range interactions. By means of a colloidal Monte Carlo approach including conformational changes of the adsorbed proteins induced by density fluctuations, we develop a scenario that is consistent with the experimentally observed three-step kinetics on specific substrates. Our observations show that not only the surface ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 34 publications
1
52
0
Order By: Relevance
“…Recently, a similar influence was detected on the adsorption kinetics of proteins [11][12][13] and the adhesion of bacteria [14]. These experiments used materials whose contribution to the potential had been tuned by means of surface stratification.…”
Section: Introductionmentioning
confidence: 67%
“…Recently, a similar influence was detected on the adsorption kinetics of proteins [11][12][13] and the adhesion of bacteria [14]. These experiments used materials whose contribution to the potential had been tuned by means of surface stratification.…”
Section: Introductionmentioning
confidence: 67%
“…This is done by defining proteins as single particles that may be spherical, disk shaped, hexagonal, or rectangular, with a specific charge or binding site located somewhere within or at the edge of the particle [138,[295][296][297][298][299][300]. The adsorption process is then simulated with a Metropolis Monte-Carlo simulation according to appropriate algorithms.…”
Section: Computational Approachesmentioning
confidence: 99%
“…It could be shown that, when interacting with a coated substrate, proteins indeed sense both, the surface layer and the underlying material: Adsorption experiments on tailored silicon wafers with differences in the thickness of the oxide layer on top of the wafers revealed qualitatively different adsorption kinetics of multiple types of proteins. 41,42 Based on Monte-Carlo simulations featuring surface processes such as surface mobility and conformational changes, the distinctions were invoked by the influence of the vdW-interactions on the time scale of these processes. 43 X-ray reflectivity experiments corroborated these findings.…”
Section: Interactions In Biological Systemsmentioning
confidence: 99%